Evaluation of the Impact of Passive Smoke on Arterial Elasticity via Echo‐Tracking Technology in a Rabbit Model. (1st November 2014) - Qiang, Yong; Ruijun, Guo; Zhen, Chen; Zhian, Li; Changyan, Lin; Xiaohui, Yang; Shu, Liu; Jie, Lin; Yuanfeng, Meng; Ruobing, Zhang; Yan, Cao; Qiao, Ma; et al.
Abstract : Objectives: The purpose of this study was to evaluate the elasticity of the abdominal aorta in passively smoking rabbits using echo‐tracking technology and pathologic examination. Methods: Fifty‐four male New Zealand White rabbits were randomly divided into a passive smoking group and a normal control group. The elasticity indicators for the abdominal aorta of the rabbits were measured by means of echo tracking, which was performed before and 1, 2, and 3 months after passive smoking. Measured indicators included the pressure‐strain elastic modulus, stiffness, arterial compliance, augmentation index, and pulse wave velocity. After the completion of the in vivo measurements, rabbits were euthanized randomly, and the corresponding arterial sites were resected for pathologic examination and in vitro measurement of vascular elasticity. Results: The echo‐tracking technology used in our research proved that the elastic modulus, stiffness, and pulse wave velocity gradually increased with time by passive smoking, whereas arterial compliance decreased by passive smoking. Pathologic examination and in vitro measurements were performed and further confirmed the observed in vivo results. Conclusions: Passive smoking can injure arteries and reduce arterial elasticity. Echo‐tracking technology is an accurate, noninvasive, and reliable method for analysis of the impact of passive smoking on arterial elasticity and detection arterial injury, which also can provide a new instructional basis for prevention and treatment of several arterial diseases.